2007
DOI: 10.1590/s1516-35982007001000023
|View full text |Cite
|
Sign up to set email alerts
|

Experimental approaches to study the nutritional value of food ingredients for dogs and cats

Abstract: This review covers methods that have been applied to study the nutrient value or quality of specific ingredients fed to dogs, cats and comparable species (i.e. foxes, minks, rats, etc.). Typically, the nutritional value or utilization of a specific ingredient is measured by total tract digestibility and has been expanded through the measurement of total nutrient balance (i.e. nitrogen or energy). However, to better understand digestion it is necessary to obtain a more accurate measurement of nutrients entering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
1
0
1
Order By: Relevance
“…En cuanto a la calidad nutrimental (tabla II), en la digestibilidad in vitro no existe diferencias estadísticamente significativas (P≤0.05) entre las muestras, pero todas tienen buena digestibilidad, por lo que se puede sugerir que al consumir este dulce se estará aprovechando el mayor contenido de proteína, así como de sus aminoácidos esenciales (Harmon, 2007). En cuanto al triptófano se observaron diferencias estadísticamente significativas (P≤0.05) entre las muestras, siendo el muégano seleccionado el que tiene mayor cantidad, esto es bueno porque este aminoácido tiene efectos sobre el sistema nervioso (Corbin, 2016).…”
Section: Resultados Y Discusiónunclassified
“…En cuanto a la calidad nutrimental (tabla II), en la digestibilidad in vitro no existe diferencias estadísticamente significativas (P≤0.05) entre las muestras, pero todas tienen buena digestibilidad, por lo que se puede sugerir que al consumir este dulce se estará aprovechando el mayor contenido de proteína, así como de sus aminoácidos esenciales (Harmon, 2007). En cuanto al triptófano se observaron diferencias estadísticamente significativas (P≤0.05) entre las muestras, siendo el muégano seleccionado el que tiene mayor cantidad, esto es bueno porque este aminoácido tiene efectos sobre el sistema nervioso (Corbin, 2016).…”
Section: Resultados Y Discusiónunclassified
“…The applicant provided many publications at this respect. Some of these publications review the use of in vitro methods and their usefulness to study the digestion in dogs (Harmon, 2007 ; De Godoy et al, 2016 ; Deschamps et al., 2022 ); others provide data on in vitro studies only (Van Zelst et al, 2015 ; Lee et al, 2017 ; Kim et al., 2021 ) or do not allow for a full comparison of the results with those obtained in vivo (Gajda et al., 2005 ); a couple describe methods that may not be comparable to the one described by Boisen in 2007 (Smeets‐Peeters et al, 1999 ; Bosch et al, 2016 ); and some were developed from Boisen's or can be considered comparable but do not provide validation of in vivo reference values at pre‐caecal level (Dufour‐Etienne et al, 1992 ; Tonglet et al, 2001 ; Hervera et al, 2007 ; Hervera et al, 2009 ; Hooda et al, 2012 ; Biagi et al, 2016 ; Penazzi et al, 2021 ). Some of the latter showed good correlation between the digestibility coefficients in vitro and in vivo (faecal data); the conditions of the studies and diets evaluated may play a major role in the correlations observed.…”
Section: Assessmentmentioning
confidence: 99%